2012
DOI: 10.1097/qad.0b013e3283568849
|View full text |Cite
|
Sign up to set email alerts
|

Memory B-cell depletion is a feature of HIV-2 infection even in the absence of detectable viremia

Abstract: These first data regarding B-cell imbalances during HIV-2 infection show that, irrespective of viremia, prolonged HIV infection leads to irreversible damage of memory B-cell homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Sugalski et al [14] further showed that serum IL-7 levels or CD4 þ T-cell frequency did not correlate with transitional or activated memory B cells percentages during chronic HCV infection, as instead reported during HIV-1 infection [13], thus suggesting that other factors may be involved in alterations of the B-cell subsets. Interestingly, production of the B-cell activating factor (Blys/BAFF) was shown to correlate with similar alteration of B cells in HCV, HIV-1, and HIV-2 infection [14][15][16][17]. Blys/BAFF may, thus, be a common factor driving abnormal activation of B-cell populations during these viral infections.…”
Section: Discussionmentioning
confidence: 94%
“…Sugalski et al [14] further showed that serum IL-7 levels or CD4 þ T-cell frequency did not correlate with transitional or activated memory B cells percentages during chronic HCV infection, as instead reported during HIV-1 infection [13], thus suggesting that other factors may be involved in alterations of the B-cell subsets. Interestingly, production of the B-cell activating factor (Blys/BAFF) was shown to correlate with similar alteration of B cells in HCV, HIV-1, and HIV-2 infection [14][15][16][17]. Blys/BAFF may, thus, be a common factor driving abnormal activation of B-cell populations during these viral infections.…”
Section: Discussionmentioning
confidence: 94%
“…This CD27+ memory B cell depletion can also occur in HIV-2-infected individuals [18]. After fractionating the CD27+ memory B cells into CD21+ cells (RM) and CD21− cells (AM), Moir S and colleagues found that while the frequencies of RM are reduced but AM are expanded in HIV-infected individuals [9].…”
Section: Hiv-associated Loss Of Classical Memory B Cellsmentioning
confidence: 99%
“…While lower GXM-reactive IgM may indicate an HIV-mediated loss of GXM-specific memory B cells [56], the higher GXMreactive IgG may signify the reactivation of a latent infection in the setting of immunosuppression in this cohort and/or the presence of cross-reactive antigens in a milieu complicated by concurrent pneumococcal, herpes, or TB infection (discussed in [52]). In a subsequent study, Subramaniam et al [53] sought to evaluate the IgM expression on memory B cells (necessary for response to encapsulated pathogens) in HIV-infected people with or without cryptococcosis, relative to healthy controls, and found that individuals with reduced IgM + memory B-cell pools, as seen in the HIV-infected, are at a greater risk for developing cryptococcosis and that the IgM + memory Bcell status may be a predictor of cryptococcal disease independent of CD4 status.…”
Section: Insights From Clinical Observationsmentioning
confidence: 98%